Short-term high-intensity interval training improves phosphocreatine recovery kinetics following moderate-intensity exercise in humans - Forbes, Sean C; Slade, Jill M; Meyer, Ronald A (Applied physiology, nutrition, and metabolism, 2008)
Previous studies have shown that high-intensity training improves biochemical markers of oxidative potential in skeletal muscle within a 2-week period. The purpose of this study was to examine the effect of short-term high-intensity interval training on the time constant ( τ) of phosphocreatine (PCr) recovery following moderate-intensity exercise, an in vivo measure of functional oxidative capacity. Seven healthy active subjects (age, 21 ± 4 years;; body mass, 69 ± 11 kg) performed 6 sessions of 4-6 maximal-effort 30 s cycling intervals within a 2-week period, and 7 subjects (age, 24 ± 5 years;; body mass, 80 ± 15 kg) served as controls. Prior to and following training, phosphorous-31 magnetic resonance spectroscopy ( 31 P-MRS; GE 3T Excite System) was used to measure relative changes in high-energy phosphates and intracellular pH of the quadriceps muscles during gated dynamic leg-extension exercise (3 cycles of 90 s exercise and 5 min of rest). A monoexponential model was used to estimate the τ of PCr recovery. The τ of PCr recovery after leg-extension exercise was reduced by 14% with high-intensity interval training (pretraining, 43 ± 14 s vs. post-training, 37 ± 15 s; p < 0.05) with no change in the control group (44 ± 12 s vs. 43 ± 12 s, respectively; p > 0.05). These findings demonstrate that short-term high-intensity interval training is an effective means of increasing functional oxidative capacity in skeletal muscle.